PENGARUH GAYA KEPEMIMPINAN KEPALA IGD TERHADAP PELAYANAN KEPADA MASYARAKAT DI RUMAH SAKIT PEMERINTAH DAERAH KABUPATEN MERANGIN JAMBI - Uying Hapid Alatas; Rizal Fadli; Iswandi Iswandi; Sukur Sukur; Musawwir Musawwir; Ifrianto Ifrianto; Diyan Andriani (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
One of the main challenges in education in Indonesia is the low competence of teachers, especially in rural areas, which impacts the quality of learning. This study aims to analyze the improvement of teacher competence through education and training (Diklat) and its impact on the quality of learning at SDN 050/VII Pauh, Sarolangun Regency. This study used a qualitative method with a case study approach, involving interviews with the principal and eight teacher respondents, observations of classroom and school activities over five days, and analysis of documentation such as training data and student grades. The results showed that training, such as the Independent Curriculum and the use of learning technology, effectively improved teachers' pedagogical (interactive methods) and professional competence. Changes were seen in student participation rates of up to 80%, average increases of 10-15% in Mathematics and Science, and non-academic achievements such as winning sports competitions. Motivational support from teachers and the principal was a contributing factor, but obstacles such as limited facilities (weak internet access, lack of teaching aids) and teachers' non-elementary school educational backgrounds hampered its optimal implementation. In conclusion, this study confirms that contextual teaching and learning-based training effectively improves teachers' pedagogical and professional competence, with a positive impact on learning quality, including increased student participation, academic grades, and non-academic achievements. However, the sustainability of the training's benefits depends on follow-up and infrastructure support. Recommendations: (1) Schools should conduct regular internal training through Teacher Working Groups (KKG) with post-training support to ensure sustainable implementation. (2) Collaboration with universities or NGOs is needed for specialized training for non-Primary Teacher Education teachers and infrastructure improvements such as internet access and teaching aids.